Safety of Modern Shipping and Requirements in Hydrographic Surveying and Nautical Charting - Pasquay, Jean-Nicolas (The International Hydrographic Review, 2015)
With the increase of ship’s draught in the sixties and the changing pattern of shipping it became quite obvious, twenty years ago, that both the status of hydrographic surveys in the world and the status of available charts were not meeting the requirements for safety of navigation. Many parts of coastal areas are as yet unsurveyed, or very scarcely surveyed, or have not been resurveyed since the lead line surveys of the last century. The paper gives the example of the state of surveys in the North Sea and indicates measures taken by the bordering countries to improve the hydrographic situation. Other parts of the world are also considered. For some parts of the world, the situation of nautical charting and nautical information has considerably deteriorated in the last 30 years, whereas the standards to meet the requirements of shipping are higher than before. Emphasis is placed on the fact that routeing measures had been designed, until recently, without careful consideration of hydrographic conditions. An unfortunate case in the Gulf of Suez is given as example. Main efforts made by the International Hydrographic Organization to improve hydrography and charting are reviewed : international chart, regional hydrographic commissions, technical assistance, cooperation with the International Maritime Organization. An insight into the use of recent techniques in order to improve quality and completeness of surveys is given. The role of automation in speeding up the process of surveys, chart production, and dissemination of nautical information is underlined. Indications on what the mariner can expect from the electronic chart complete the article. The article concludes that modern techniques by themselves are unable to narrow the present gap between navigational requirements and the state of hydrography. More coastal States must become aware of the situation and its risks and must have the will to use the means to face the challenge.